Unfolding the Mystery of Endemic Eye Disease of Nepal: Fifty Years of SHAPU, the Seasonal HyperAcute PanUveitis - Joshi, Purushottam; Sitaula, Ranju Kharel; Manandhar, Anu (Nepalese Journal of Ophthalmology, 2024)
Half a century on, first reported in 1975 by Professor (Prof.) Doctor (Dr.) Om Krishna Malla as Seasonal Endophthalmitis (Malla OK, 1978; Malla OK, 2005); and named as Seasonal HyperAcute PanUveitis (SHAPU) in 1979 by Prof. Dr. Madan Prasad Upadhyay (Upadhyay et al., 1979), the mystery of SHAPU continues to unfold, but the enigma persists. As another potential outbreak of SHAPU is expected this year, let this be a call to action: to collaborate, to increase awareness, to investigate, to establish pathogenesis, to treat, and be prepared to manage this endemic disease of Nepal efficiently and effectively; ultimately, to protect the vision of the vulnerable.